2020
DOI: 10.1109/jstars.2020.3023549
|View full text |Cite
|
Sign up to set email alerts
|

Road Extraction Methods in High-Resolution Remote Sensing Images: A Comprehensive Review

Abstract: Road extraction from high-resolution remote sensing images (HRSI) is a challenging but hot research topic in the past decades. A large number of methods are invented to deal with this problem. This article provides a comprehensive review of these existing approaches. We classified the methods into heuristic and data-driven. The heuristic methods are the mainstream in the early years, and the data-driven methods based on deep learning have been quickly developed recently. With regard to the heuristic methods, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(51 citation statements)
references
References 130 publications
0
51
0
Order By: Relevance
“…With a total area of 164,422 km 2 , twice the size of Ireland, the State is divided into 22 municipalities (Figure 1). Approximately 63% (101,645 km 2 ) of its territory is covered by protected areas, consisting of Conservation Units (Federal, State, and Municipal) with 48% (77,744 km 2 ) and Indigenous Lands with 15% (23,901 km 2 ) [14]. Additionally, almost 10% (15,039 km 2 ) of the State was deforested by 2019, the sixth-highest among Brazilian Amazon states [21].…”
Section: Characterization Of the Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…With a total area of 164,422 km 2 , twice the size of Ireland, the State is divided into 22 municipalities (Figure 1). Approximately 63% (101,645 km 2 ) of its territory is covered by protected areas, consisting of Conservation Units (Federal, State, and Municipal) with 48% (77,744 km 2 ) and Indigenous Lands with 15% (23,901 km 2 ) [14]. Additionally, almost 10% (15,039 km 2 ) of the State was deforested by 2019, the sixth-highest among Brazilian Amazon states [21].…”
Section: Characterization Of the Study Areamentioning
confidence: 99%
“…The dynamics of opening or building unofficial roads can occur through narrow paths and forest areas that make detection difficult, requiring high-resolution images and improved image processing techniques [16,17]. Some recent studies have shown that Deep Learning techniques can automatically extract roads from high spatial resolution satellite images with high accuracy [14,25]. However, few studies have applied these techniques in the Amazon.…”
Section: Road Mapping In the Southwestern Amazon: Advances And Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the recent development in artificial intelligence, especially deep learning technology, new ideas have been provided for road extraction [3]. Deep learning was developed Remote Sens.…”
Section: Introductionmentioning
confidence: 99%
“…2021, 13, 90 2 of 18 from research of neural networks and has made significant advancements in computer vision [4,5] and other fields. It has shown great advantages in image scene classification [6,7], target detection [8,9] and semantic segmentation [10][11][12]; the latter is a useful tool for road extraction [3] so we use it here as the basis for our method. However, from the perspective of practical applications, there are many special issues that need to be studied.…”
Section: Introductionmentioning
confidence: 99%